Analysis of railway infrastructure with parallel courses for direction Znamyanka–Odessa - Vernyhora, R. V.; Papakhov, O. Yu.; Logvinova, N. O. (Science and Transport Progress, 2012)
Introduction. A ground for optimization of vehicular work on direction Znamyanka–Odessa is related to distributing the transportation process over parallel courses and introducing the energy saving technology. Analysis of dynamics of changes in flows of goods and trains directed to ports of the Odessa region: Analysis of basic toplevel loads which leave ports of the Odessa region for export. Organization of car traffic volumes in freight trains determined by the level of load of transport technical means, distributing the sorting and marshalling work among the station and points of departure. Organization of passing the car traffic volumes is characterized by uneven correlation of run of empty cars to the general freight run. Analysis of density of car traffic volumes. Analysis of railway infrastructure on direction with parallel courses Znamyanka–Odessa: Infrastructure of railway direction Znamya–Odessa allows organizing the traffic of trains jointly on the track section Znamyanka–Pomoshnaya with the subsequent dividing into two parallel directions: Pomoshnaya–Kolosovka–Odessa-sorting and Pomoshnaya–Kotovsk–Razdelnaya–Odessa-Zastava-1. The analysis of traffic amounts of passenger and freight trains is conducted on parallel courses of direction for period 2000–2011. Conclusion: The necessity of redistribution of train traffic volumes from the basic direction to auxiliary one is grounded that will allow selecting the reserve of carrying capacity for organization of motion of high-speed passenger trains.